Pengaruh Kompetensi Dan Latar Belakang Pendidikan Terhadap Produktivitas Kerja Pegawai Dinas Perikanan Kabupaten Pesawaran - Paramita N, Maria; Cahyo N, Yudhinanto Cahyo N; Rini, Prima (LPPM STIE KRAKATAU, 2024)
This study aims to determine the effect of competence and educational background on employee productivity in the Pesawaran Regency Fisheries Service. The data used in this study is primary data data obtained from the source, namely through respondents who fill out questionnaires. The analysis technique is done through validity, reliability, classical assumptions, hypotheses and multiple linear regression. Based on the analysis, it can be concluded that simultaneously the influence of competence and educational background has a significant and positive effect on employee work productivity in the Pesawaran Regency Fisheries Service, and partially each variable has a significant effect on employee work productivity. Thus to increase work productivity must pay attention to competency factors and educational factors